Compact metamaterial antenna for UWB applications. Issue 16 (1st August 2015) - Islam, M.M.; Islam, M.T.; Samsuzzaman, M.; Faruque, M.R.I.
Abstract : A compact antenna is proposed using planar‐patterned metamaterial structures for ultra‐wideband applications. This antenna consists of four metamaterial unit cells that simultaneously show both negative permeability and negative permittivity on the triangular patch and three rectangular slots on the partial ground plane fed with a microstrip line. It has a wide bandwidth from 3.07 to 19.91 GHz for voltage standing wave ratio (VSWR) <2 and an average gain of 5.62 dBi with a peak of 8.57 dBi because of using planar‐patterned metamaterial structures. Good agreement between computations and experiments is realised convincing that the antenna can operate over a wide bandwidth with planar‐patterned metamaterial structures and compact size (0.28 λ × 0.19 λ × 0.02 λ ).